Making laws for cyberspace / Chris Reed. - Reed, Chris 1956- (Oxford : Oxford University Press, 2012)
Command and control -- The route to lawfulness -- Extraterritoriality -- Enforcing law in cyberspace -- Sources of authortiy -- Authoritative law-making -- Cyberspace communities and cyberspace norms -- Three ways to make meaningless law -- Mismatch with cyber reality -- Aims and effectiveness -- Future-proofing -- Revisiting the modalities of regulation -- Making laws for cyberspace.